Two differential binding mechanisms of FG-nucleoporins and nuclear transport receptors - Tan, Piau Siong; Mercadante, Davide; Gräter, Frauke (Cell reports, 2018)
Summary - Phenylalanine-glycine-rich nucleoporins (FG-Nups) are intrinsically disordered proteins, constituting the selective barrier of the nuclear pore complex (NPC). Previous studies showed that nuclear transport receptors (NTRs) were found to interact with FG-Nups by forming an “archetypal-fuzzy” complex through the rapid formation and breakage of interactions with many individual FG motifs. Here, we use single-molecule studies combined with atomistic simulations to show that, in sharp contrast, FG-Nup214 undergoes a coupled reconfiguration-binding mechanism when interacting with the export receptor CRM1. Association and dissociation rate constants are more than an order of magnitude lower than in the archetypal-fuzzy complex between FG-Nup153 and NTRs. Unexpectedly, this behavior appears not to be encoded selectively into CRM1 but rather into the FG-Nup214 sequence. The same distinct binding mechanisms are unperturbed in O-linked β-N-acetylglucosamine-modified FG-Nups. Our results have implications for differential roles of distinctly spatially distributed FG-Nup⋅NTR interactions in the cell.
Gesehen am 08.05.2019